FACTORS AFFECTING INTEREST RATE AND ITS RELATION WITH BANKS’ PROFITABILITY - Ali, Barzan Omar (Accounting Department,, 2018)
The aim of this study is to investigate the factors influencing interest rates and its relationship with private banks profitability in Erbil. The research was conducted at private banks in Erbil. The researcher attempted to find out the most of significance factor that affects interest rates and its relationship with banks Profitability. However, the researcher gathered data from employees at different level of management at private banks in Erbil. The researcher distributed 300 questionnaires, but only 238 questionnaires were received from employees and been completed. The researcher used a quantitative research method to find out the most of significance factor that affects interest rates and its relationship with banks Profitability. The findings of multiple regression analysis revealed that the highest value was for economic growth, the B value =.812, this indicates that economic growth significantly and positively effects interest rates as a result maximize bank’s Profitability.